2021
DOI: 10.1111/ejn.15179
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing the contribution of sensory cues in social approach

Abstract: Although considerable progress has been made regarding our understanding of same-sex conspecific and non-aggressive interactions (Gunaydin et al., 2014;Puglisi-Allegra & Cabib, 1997;Robinson et al., 2002Robinson et al., , 2011, questions regarding the contribution of sensory cues in social approach and their specific neurobiological correlates remain open. When

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Employing strategies capable of labelling defined LHb neuronal populations either based on their genetic profile or connectivity may represent a way to isolate LHb neuronal modules that could participate in specific facets of social interactions. The LHb directly controls monoaminergic nuclei including the dopaminergic ventral tegmental area (VTA), which is crucial for social interaction [ 48 ] (Fig. 1a, b ).…”
Section: Lateral Habenula Contribution To Innate Behavioursmentioning
confidence: 99%
“…Employing strategies capable of labelling defined LHb neuronal populations either based on their genetic profile or connectivity may represent a way to isolate LHb neuronal modules that could participate in specific facets of social interactions. The LHb directly controls monoaminergic nuclei including the dopaminergic ventral tegmental area (VTA), which is crucial for social interaction [ 48 ] (Fig. 1a, b ).…”
Section: Lateral Habenula Contribution To Innate Behavioursmentioning
confidence: 99%
“…In recent three-chamber research, similar results are found. The activity from dopaminergic neurons of the ventral tegmental area was an increase when toward a juvenile mouse other than an object with social odor [38]. Thus, studies of animal experiments offer a favorable reference for exploring the IPD neural mechanism of human beings.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study (21) we suggested that similarly different patterns of transitions between SD rats and C57BL/6J mice reflect their distinct dynamics of social motivation. Accordingly, a recent study found a specifically high level of activity in dopaminergic neurons of the ventral tegmental area (VTA) during transition from object to social stimuli (30). Thus, the strain-dependent distinct patterns of transitions found by us may reflect distinct dynamics of social motivation between the strains.…”
Section: Discussionmentioning
confidence: 49%
“…Sex-dependent differences in murine social behavior have been comprehensively explored in previous studies, but this was done mainly regarding hormonal-driven aspects of social behavior (26,27), such as sexual ( 28), anxiety/aggressive (10), and parental behaviors (29). In contrast, evidence for differences in other aspects, such as social preference and social novelty preference have been reported only anecdotally, and in some cases with contradicting results (see for example 22,30). Here, we systematically explored such differences across three types of social discrimination tasks and three distinct laboratory mouse strains.…”
Section: Discussionmentioning
confidence: 99%